(3GdYjhf aj CNHGQ Ydi Hf ehSi GdQVi Hf ehSi GdcGXe GHf LYaQ GdUGObs - (3eMeO Hf Ydj Hf GdMSjf Hf ehSi Hf HCHhjg Gdbejs ((3Ydi Hf UdGM GdfLO s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ , GdYRjR GdLHGQ , GdQMje GdZaGQ , aGWQ GdCQV hGdSeGA , NGdb GdXdeI hGdVjGA , ebOQ GdCRefI hGdOghQ s
(3BNQgG (B:s
(3hbO BdjJ Ydi faSI Ydi Cf dG CaGQb gPG GdeTgO eG HbjJ Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQI s
(3HChdgG agQSJ ddehVhYGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs